Patterns for Creative Thinking (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
Creative thinking can be learned in the same way as analytical thinking. Many creative thinking tools are highly structured and the same methodical patterns occur again and again. This paper is a start to collect and connect the basic patterns of creative thinking. It will not present any new method but will try to generalize the commonalities of similar methods and approaches. There are many descriptions of creativity methods and tools out there. What motivates the description as patterns is the generalization of similar methods, the reasoning for the actual form in terms of forces, and the contextualization and connection of the methods/tools. Very often a specific method implies other methods to follow up or it can be combined with other methods. A pattern language captures such relations.